2018
DOI: 10.1021/acs.est.8b04383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HCO3 on Degradation of Toxic Contaminants of Emerging Concern by UV/NO3

Abstract: This study investigated the significant influence of HCO3 – on the degradation of contaminants of emerging concern (CECs) during nitrate photolysis at 254 nm for water reuse applications. The second-order rate constants for the reactions between selected contaminants with carbonate radical (CO3 •–) were determined at pH 8.8 and T = 20 °C: estrone ((5.3 ± 1.1) × 108 M–1 s–1), bisphenol A ((2.8 ± 0.2) × 108 M–1 s–1), 17α-ethynylestradiol ((1.6 ± 0.3) × 108 M–1 s–1), triclosan ((4.2 ± 1.4) × 107 M–1 s–1), diclofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(62 citation statements)
references
References 67 publications
1
61
0
Order By: Relevance
“…40,41 Although the second-order rate constant of DCF with CO 3 c À (k CO3 À =DCF ¼ ð2:7 AE 0:7Þ Â 10 7 M À1 s À142 ) was lower than those with SO 4 c À (k SO4 À =DCF ¼ ð9:2 AE 0:6Þ Â 10 9 M À1 s À143 ) and HOc (k HOc/DCF ¼ (7.5 AE 1.5) Â 10 9 M À1 s À111 ), its steady-state concentration might be higher in the reaction system due to its selectivity, 44 resulting in a positive effect of CO 3 2À on DCF degradation. Similar nding was also reported by Huang et al 42 in DCF degradation by UV/NO 3 À in the presence of HCO 3…”
Section: Effect Of Initial Ps Dosagesupporting
confidence: 90%
“…40,41 Although the second-order rate constant of DCF with CO 3 c À (k CO3 À =DCF ¼ ð2:7 AE 0:7Þ Â 10 7 M À1 s À142 ) was lower than those with SO 4 c À (k SO4 À =DCF ¼ ð9:2 AE 0:6Þ Â 10 9 M À1 s À143 ) and HOc (k HOc/DCF ¼ (7.5 AE 1.5) Â 10 9 M À1 s À111 ), its steady-state concentration might be higher in the reaction system due to its selectivity, 44 resulting in a positive effect of CO 3 2À on DCF degradation. Similar nding was also reported by Huang et al 42 in DCF degradation by UV/NO 3 À in the presence of HCO 3…”
Section: Effect Of Initial Ps Dosagesupporting
confidence: 90%
“…This was mainly because NO 3 À could be excited to produce HOc under UV irradiation as shown in eqn (12)-(15). 42 Huang et al 43 also found that compared with UV alone, UV/NO 3 À signicantly promoted the elimination of DCF, which was due to the contribution of HOc. The presence of HCO 3 À enhanced the removal of DCF, and the promotion effect was gradually increased with the increase of HCO 3 À concentration, as presented in Fig.…”
Section: Effect Of Initial Concentration Of Dcfmentioning
confidence: 95%
“…The photocatalytic azolylation reaction of estrone methyl ether, a precursor leading to an FDA‐approved oral contraceptive (mestranol), has been reported by Weaver and co‐workers and they were able to isolate the desired estrone derivative in 37% yield as a single regioisomer in which the benzothiazolylation occurred at C 4 position of the estrone 3‐methyl ether (23). Recently, the photodegradation of estrone and 17α‐ethinylestradiol with HCO 3 − , NO 3 − and 254 nm photolysis has been reported (24) because these steroids are considered as toxic contaminants of emerging concerns (CECs) for water reused applications. Estrogens were also photooxidized efficiently with humic acids in the presence of Mn(III) (25) and the application of alkene cyclopropanation with chloromethyl silicate through a visible‐light‐mediated redox neutral catalysis of vinylphosphonate derived from estrone took place efficiently and the photoproduct was isolated in 92% yield (26).…”
Section: Introductionmentioning
confidence: 99%